Diagnosis and management of vasovagal syncope: A comprehensive review - Veliawan, Zhafran; Rizal, Ardian (Heart Science Journal, 2026)
Syncope is a distinct type of  transient loss of consciousness characterized by rapid onset and complete spontaneous recovery. Syncope is categorized into three different kinds according to the 2018 European Society of Cardiology guidelines. Different types of syncope ultimately converge on a common pathophysiological occurrence: global cerebral hypoperfusion, resulting from the circulatory system's inability to maintain blood pressure at a level sufficient to provide adequate cerebral perfusion. Vasovagal syncope, often referred to as the "common faint," is the predominant etiology of syncope. Although classified as a benign condition, recurrent syncope incurs significant costs and adversely effects the quality of life for patients, particularly in the elderly. Typical vasovagal syncope predominantly manifests in young adults and is frequently identified based on medical history, provided there is no structural heart disease. Atypical vasovagal syncope frequently presents with a short or nonexistent prodrome, and inattention regarding the loss of consciousness is prevalent, leading to potential misdiagnosis, such as falls. This article provides an overview of the evaluation and management of vasovagal syncope.